2015
DOI: 10.1177/0954411915606484
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the structural behaviour of colonic segments by inflation tests: Experimental activity and physio-mechanical model

Abstract: A coupled experimental and computational approach is provided for the identification of the structural behaviour of gastrointestinal regions, accounting for both elastic and visco-elastic properties. The developed procedure is applied to characterize the mechanics of gastrointestinal samples from pig colons. Experimental data about the structural behaviour of colonic segments are provided by inflation tests. Different inflation processes are performed according to progressively increasing top pressure conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…They used small intestinal inflation data aimed at studying stress relaxation [98] and demonstrated that their model was able to reproduce the experimental data with a neo-Hookean formulation for Ψ E and Ψ OE in conjunction with either linear or non-linear viscous models (it was not specified which performed better). They used colonic inflation data aimed at studying creep [99] and demonstrated that their model was able to reproduce the experimental data with a Humphrey model (we classified as Fung-type) for Ψ E and Ψ OE along with a linear viscous model. They used rectal inflation data aimed at studying the behavior of the rectum under normal conditions and Hirschsprung's disease [100], and demonstrated that their model was able to reproduce the experimental data for healthy and diseased tissue with a neo-Hookean formulation for Ψ E and Ψ OE along with a linear viscous model.…”
Section: Viscous and Visco-hyperelastic Modelsmentioning
confidence: 99%
“…They used small intestinal inflation data aimed at studying stress relaxation [98] and demonstrated that their model was able to reproduce the experimental data with a neo-Hookean formulation for Ψ E and Ψ OE in conjunction with either linear or non-linear viscous models (it was not specified which performed better). They used colonic inflation data aimed at studying creep [99] and demonstrated that their model was able to reproduce the experimental data with a Humphrey model (we classified as Fung-type) for Ψ E and Ψ OE along with a linear viscous model. They used rectal inflation data aimed at studying the behavior of the rectum under normal conditions and Hirschsprung's disease [100], and demonstrated that their model was able to reproduce the experimental data for healthy and diseased tissue with a neo-Hookean formulation for Ψ E and Ψ OE along with a linear viscous model.…”
Section: Viscous and Visco-hyperelastic Modelsmentioning
confidence: 99%
“…In the case of hollow organs, general experimental activities pertain to the mechanical and structural characterization of the specific anatomical district: mechanical tests at the tissues level [31][32][33][34], such as tensile, compression, and shear tests for the investigation of nonlinear elasticity and damage phenomena; stress relaxation and creep tests for the identification of the viscoelastic behavior; mechanical tests at the sub-structural level, such as membrane indentation tests for the evaluation of in-plane bending behavior, and opening angle tests for the identification of residual stresses [35][36][37]; mechanical tests at the structural level, such as inflation tests, for the evaluation of the pressure-volume response, and flow tests for the identification of fluid-dynamic quantities and fluid-structure interaction phenomena [38][39][40][41]. Aiming to evaluate the effects of diagnostic and surgical procedures, specific experimentations can be performed.…”
mentioning
confidence: 99%